The Link Between Industry Value Added and Electricity Consumption - Tapsın, Gulcin (European Scientific Journal, ESJ, 2017)
This study aims to analyse the link between industry value added and electricity consumption in Turkey for the years between 1970 and 2015. The sectoral distribution of net electricity consumption has been obtained from Turkey Electricity Distribution and Consumption Statistics on GWh basis while industry value added data have been obtained from World Development Indicators’ data bases on dollar basis with the fixed prices of the year 2012. The correlations between the variables have been examined by means of Johansen cointegration test and error correction model. According to the results of the study, it has been seen that there exists bidirectional relationship between the electricity consumption and value added variable in the long term. On the other hand, in terms of the Error Correction Model used for a short-term relationship, no short-term relationship has been identified between the variables.